Unraveling The Social And Economic Dimensions In Determining The Selling Price Of Makeup Artist Services (MUA) - Yuly Azahra; Sugianto Sugianto; Nina Yusnita Yamin; Ernawaty Usman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to uncover the factors that determine the selling price of Make Up Artist (MUA) services. Using a qualitative approach with a case study method, data was collected through in-depth interviews, observations, and documentation on the two main informants who were purposively selected. Data analysis was carried out thematically with coding techniques to identify pricing patterns. The results of the study identified six main themes that affect the pricing of MUA services: (1) Motivation as the foundation of professionalism and the determination of service value; (2) The type of service that correlates with the complexity and duration of the work; (3) Pricing Strategy that takes into account quality, market demand, and customer expectations; (4) The Role of Social Media and Testimonials in Building a Professional Image and Price Legitimacy; (5) Ethics and Professionalism as the foundation for maintaining price fairness; and (6) Challenges related to consumer purchasing power, reputation, and consistency of service quality. These findings confirm that the price of MUA services is a multidimensional construct, determined not only by cost-based economic calculations, but also by social and symbolic factors that reflect skills, professional image, and perceived value by consumers. Theoretically, this study enriches the pricing literature in the creative services industry driven by personal branding and non-monetary value. Practically, the results of this study provide strategic implications for MUA actors to formulate a fair, competitive, and sustainable price structure.